High and Low Molecular Weight Hyaluronic Acid Affect the Expression of Surface Molecules by Monocytes Stimulated with Porphyromonas gingivalis In vitro - Edson Costa e Silva; Hércules Henrique Onibene Castro; Luara Isabela dos Santos; Lis Ribeiro do Vale Antonelli; Natália Rocha Guimarães; Paula Prazeres Magalhães; Luiz De Macêdo Farias; Martinho Campolina Rebello Horta; Jôice Dias Corrêa; Paulo Eduardo Alencar Souza (Archives of Current Research International, 2025)
Aims: Hyaluronic acid (HA) has been used as an adjunct in the treatment of periodontal disease. HA molecules of different molecular weights act on different cell types, inducing differentiation, activation, migration, and production of inflammatory mediators. The aim of this study was to evaluate the effect of low (LMWHA) and high (HMWHA) molecular weight HA on the expression of costimulatory molecules and toll-like receptors by monocyte subpopulations stimulated in vitro with Porphyromonas gingivalis (Pg). Study Design: In vitro experimental study. Place and Duration of Study: Laboratory of Biology and Immunology of Infectious and Parasitic Diseases, Instituto René Rachou, Fiocruz Minas, between 2018 and 2019. Methodology: Peripheral blood mononuclear cells (PBMCs) from 10 donors were stimulated with Pg during 1 hour and then incubated with 0.2% LMWHA or HMWHA for another sixteen hours. Immunostaining and flow cytometry were performed for detection of CD40, CD80, CD86, HLA-DR, TLR2 and TLR4 expression by CD14+ monocytes and subpopulations of classical (CD14+CD16-) and non-classical/intermediate monocytes (CD14+CD16+). Results: LMWHA or HMWHA increased TLR2 and reduced TLR4 expression, but did not affect CD40, CD80, CD86 or HLA-DR in total and classical monocytes. Considering Pg-stimulated cells, HMWHA increased the expression of CD40, HLA-DR and TLR2 in non-classical/intermediate monocytes. Conclusion: The effect of HA used topically in the periodontal tissues seems to directly involve modulation of surface molecules responsible for cell signaling and control of periodontal immunoinflammatory processes.